Divergent immune responses to synthetic and biological scaffolds. (February 2019) - Sadtler, Kaitlyn; Wolf, Matthew T.; Ganguly, Sudipto; Moad, Christopher A.; Chung, Liam; Majumdar, Shoumyo; Housseau, Franck; Pardoll, Drew M.; Elisseeff, Jennifer H.
Abstract: The immune system plays a critical role in wound healing and the response to biomaterials. Biomaterials-directed regenerative immunology is an immunoengineering strategy that targets the immune system to promote tissue repair. Biomaterial scaffolds employed in regenerative medicine can be broadly classified as biological (such as those derived from the tissue extracellular matrix) or synthetic. Here, we show in depth the divergent myeloid response to biological versus synthetic biomaterial scaffolds. While neutrophil depletion and changes in physical properties such as shape and mechanics can modulate the pro-inflammatory myeloid immune response to synthetic materials to a degree, the overall general divergent myeloid responses persist. Biologic scaffolds elicit a type-2-like immune response with upregulation of genes such as Il4, Cd163, Mrc1 and Chil3, as well as genes associated with damage-associated molecular patterns providing another possible mechanism by which ECM scaffolds promote wound healing via amplification of endogenous wound-associated signaling pathways. Synthetic materials recruit a high proportion of neutrophils which is compounded by material stiffness and by the presence of an injury. Understanding the complex immune response to biomaterial classes will help in the efficient design of immunoengineering strategies and optimizing regenerative and reducing foreign body fibrotic responses to scaffolds.